Nanoengineerded cell membrane-based nanoparticles for tumor and immunocompetent cells modulation - Comparetti, Edson José (2021)
In 2020, cancer caused 10 millions of deaths and 17 million new diagnoses have been registered worldwide. Human hepatocellular carcinoma, pancreatic carcinoma, and prostate carcinoma were the third, seventh, and eighth neoplasms, respectively, with the highest casualties, with the frequency of relapses and metastasis requiring the development of new therapeutic procedures. Amid scientific and technological innovation that contribute to patient survival, nanomedicine and immunotherapy are responsible for the most satisfactory clinical results, creating new therapies currently applied to chronic diseases. Although neoplastic cells have the ability to evade immune surveillance and to modulate tumor microenvironment, nanocomposites are capable to prevent expression of immunosuppressive proteins and to increase cellular immunity. Recent advances in nanoengineering use the main components from cell membrane to create nanovesicles to deliver a large amount of antigenic material to antigen-presenting cells (APC). In the blood, phagocytic cells impair particles deposition in target sites, activating inflammatory response to modulate tumor microenvironment. Instead of targeting tumor mass, nanostructures are expected to re-educate the immune system and to increase the major mechanisms in circulatory system and peripheral lymphoid organs, helping to repair leukocytes activity lost after exposure to suppressive stimulus. In this thesis we synthesized nanoparticles with lipids and proteins from plasma membrane of hepatic neoplastic cells and pancreatic cancer cells (MNPs), aiming at developing nanocarriers to transport antineoplastic and immunomodulatory agents. We combined MNPs with first-line drugs used in clinical treatment (gemcitabine (GEM), paclitaxel (PTX), cabazitaxel (CTX)) to produce a cytotoxic response in cancer cells, and with an oligonucleotide sequence (siRNA) from an oncogene, to establish a pro-inflammatory response in human peripheral blood monocytes. The nanoparticles were used to deliver antineoplastic agents to cancer cells, as well as to and deliver antigenic material to antigen-presenting cells for modulating immune system and promote an inflammatory response in the tumor sites. A discuss on the nanoparticles modulatory mechanisms and their effects on cancer immunogenicity is presented, investigating the next-generation of nanomaterials developed to decrease the neoplastic cells ability of evading surveillance system.